Cholinesterase Research - Korabecny, Jan; Soukup, Ondrej (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This collection of 10 papers includes original as well as review articles focused on the cholinesterase structural aspects, drug design and development of novel cholinesterase ligands, but also contains papers focused on the natural compounds and their effect on the cholinergic system and unexplored effects of donepezil.